(3QSGdI GdeSJHUQs - (3GdYQHj , eMeO Hf YHO Gddg GdYQHj GdMfaj,J (B985 (3g` s
(3ChdgG (B:s
(3bGd GdEeGe Hf GdYQHi gPg QSGdI GdeSJHUQ s
(3BNQgG (B:s
(3jfJgi HhbaI cGJH hBNQ eG ajg bhdg (B: (3hjJHjf dc Cf eYQaI GdQH Jchf HGdYde s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B226s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs